Fostering Effective Communication: Exploring Students' Views on the Group Investigations to Enhance Arabic Speaking Skills - Rahimah (PT FORMOSA CENDEKIA GLOBAL, 2024)
The Arabic language has become strategically important in the era of globalization, which demands multilingual competence. However, developing Arabic speaking skills is often perceived as complex and uninteresting for students. Therefore, this research aims to evaluate the effectiveness of Cooperative Learning Methods, precisely the Group Investigations approach, in enhancing students' Arabic speaking abilities in secondary schools. This study employs a mixed-method approach. The research sample consists of 30 eighth-grade students from a secondary school. The results indicate that cooperative learning methods, particularly the Group Investigations approach, can effectively improve students' Arabic speaking abilities. These findings underscore the importance of adopting engaging and student-involved teaching methods in the Arabic language learning process in the classroom